PENERAPAN KURIKULUM PERPADUAN AGAMA DAN UMUM (STUDI KASUS DI MTSN 3 UNGGULAN TAMBAKBERAS JOMBANG) - Yusuf, Faqihuddin Nidlom Syah; Chotimah, Chusnul (JoEMS (Journal of Education and Management Studies), 2021)
Curriculum integration is an effort to improve the quality of education in teaching and learning activities in schools. One of the curriculum blends developed in learning at MTsN 3 Unggulan Jombang is the combination of the Ministry of Religion curriculum combined with the Islamic boarding school curriculum which is implemented in the learning process. In order to develop the quality and quality of madrasah, the Ministry of Religion curriculum and Islamic boarding school curriculum were developed into several excellent programs. So that the goals of education will be clearer in the direction to be taken. To add insight, MTsN 3 Jombang has its own advantages in its curriculum, including in each semester there are comparative studies out of town and even abroad, as well as Arabic and English language days.